Desain Pendidikan Agama Islam dalam Keluarga - Tafsir, Ahmad; Suhartini, Andewi; Rahmadi, Aji (Laboratory of Islamic Religious Education Faculty of Tarbiyah and Teacher, 2020)
Islamic religious education in the family runs throughout the ages, through the process of implementing daily life in the family. The substance of religious education in the family is the role of parents paying attention to their children as their substitutes in the future. So the process of Islamic religious education in the family is very important. Islamic religious education is a shared responsibility, especially parents, because preparing the child's future becomes the responsibility of parents both in terms of psychological, physical, educational, child health and religiousness. The design of Islamic religious education is the practice of educational planning to help in the transfer of knowledge and the inculcation of religious values in full and continuity, to form a Muslim person who is obedient to his God and becomes a Muslim person who is useful to society. Â AbstrakÂ Pendidikan agama Islam dalam keluarga berjalan sepanjang masa, melalui proses implementasi kehidupan sehari-hari dalam keluarga. Substansi pendidikan agama dalam keluarga dalah bagaiman peran orang tua mencurahkan perhatian kepada anak-anak mereka sebagai pengganti mereka di masa yang akan datang. Sehingga proses pendidikan agama Islam dalam keluarga sangatlah penting.Â Pendidikan agama Islam merupakan tanggung jawab bersama terutama orang tua, karena menyiapkan masa depan anak menjadi tanggung jawab orang tua baik dari sisi psikologis, fisik, pendidikan, kesahatan dan religiusitas anak. Desain pendidikan agma Islam adalah praktek perencanaan pendidikan untuk membantu agar dapat terjadi transfer ilmu pengetahuan dan penanaman nilai-nilai kegamaan secara utuh dan kontinuitas, untuk membentuk pribadi muslim yang taat kepada Tuhannya dan menjadi pribadi muslim yang berguna bagi masyarakat.